2009
DOI: 10.4049/jimmunol.0901073
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Stromal Fibroblasts to IFN-γ Blocks Tumor Growth via Angiostasis

Abstract: The importance of stromal cells for tumor is akin to soil for seed. However, the interaction among these cells is far from understood. In this study, we show that stromal fibroblasts exist not only during tumor progression but also during regression stage, together with immune effector cells. Coinjection of stromal fibroblasts with tumor cells often promotes tumor growth. However, the presence of IFN-γ significantly impairs the ability of these cells to promote tumor growth due to a reduced angiogenesis. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 46 publications
1
56
0
1
Order By: Relevance
“…Both cytokines have been shown to promote innate and adaptive antitumor immune responses (10). Moreover, they act directly or indirectly through inflammatory cells on tumor blood vessels (11)(12)(13). Most notably, high-dose TNFα disrupts angiogenic vessels and is used in isolated limb perfusion to treat locally advanced melanoma and soft tissue sarcoma (14).…”
mentioning
confidence: 99%
“…Both cytokines have been shown to promote innate and adaptive antitumor immune responses (10). Moreover, they act directly or indirectly through inflammatory cells on tumor blood vessels (11)(12)(13). Most notably, high-dose TNFα disrupts angiogenic vessels and is used in isolated limb perfusion to treat locally advanced melanoma and soft tissue sarcoma (14).…”
mentioning
confidence: 99%
“…TNF-α is important in inhibiting tumor growth in most tumors [65]. IFN-γ is mainly secreted by NK cells, which is relevant for inhibiting tumor growth in non-inflammatory-induced tumors [66]. Consequently, the reduction of cytokines with tumor killing may represent another mechanism by which HLA-G can exert its immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to highly species specificity, human unlikely exerts direct effects on murine vascular system, but likely acts on tumor cells to indirectly regulate angiogenesis. It was reported that IFN-γ acted as antiangiogenic cytokine by inhibiting the expression of angiogenic factors, such as VEGF or perlecan, in renal cell carcinoma [36], stromal fibroblasts [37], human cornea [38], and WiDr/HT29 colon carcinoma cells[39], or by inducing the expression of anti-angiogenic factor monokine induced by interferon-gamma (MIG, or CXCL9) in non-small cell lung carcinom [40]. Here we would like to make a hypothesis that IFN-γ may exert antiangiogenic effect in nude mice carrying NPC xenografts by regulating the expression of some angiogenic or antiangiogenic factors in NPC cells.…”
Section: Discussionmentioning
confidence: 99%